Fluorescent pseudomonads from plant rhizosphere as biological agent to control white root disease and growth-promoting on rubber plants - HUSDA MARWAN; Sri Mulyati; S Sarman; Islah Hayati (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Marwan H, Mulyati S, Sarman S, Hayati I. 2020. Fluorescent pseudomonads from plant rhizosphere as biological agents to control white root disease and growth-promoting on rubber plants. Biodiversitas 21: 5338-5343. White root disease (Rigidoporus lignosus) is a serious problem of rubber plantation in Indonesia, including in Sumatera. The fungal infection is often difficult to detect, infection develops rapidly and can cause plant death if left untreated since the early stage, and thus using biological agents might be an efficient way to overcome the disease. This research was aimed to explore fluorescent pseudomonads from rubber plant rhizosphere that can inhibit the growth of the fungal pathogen, characterize fluorescent pseudomonads isolated as biological control agent and plant growth promoter, and apply the isolate to rubber plants to control the disease and growth of plants. Twelve out of the 76 fluorescent pseudomonads isolated from several rhizospheres of rubber plants were found to be antagonistic to white root fungi. Fluorescent pseudomonads have various characteristics such as chitinolytic activity, phosphate solvent, and nitrogen fixation. The application of the antagonistic isolates on rubber seedlings was able to increase growth and suppress the colonization of R. lignosus on rubber plant roots.